2009
DOI: 10.1371/journal.pone.0005953
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated AMPA Receptor Expression Allows Glioblastoma Cell Survival in Glutamate-Rich Environment

Abstract: BackgroundGlioblastoma multiforme (GBM) cells secrete large amounts of glutamate that can trigger AMPA-type glutamate receptors (AMPARs). This commonly results in Na+ and Ca2+-permeability and thereby in excitotoxic cell death of the surrounding neurons. Here we investigated how the GBM cells themselves survive in a glutamate-rich environment.Methods and Findings In silico analysis of published reports shows down-regulation of all ionotropic glutamate receptors in GBM as compared to normal brain. In vitro, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
(36 reference statements)
3
20
0
2
Order By: Relevance
“…Reduced glutamate receptor phosphorylation, previously observed in GBM (35, 36), along with decreased phosphorylation of Dlg 2 (PSD-93), 3, and 4 (PSD-95) (37), and other neuron-specific proteins in our tumors likely reflect the differences in cellular composition between glioma and normal brain tissue (21). By comparison, phosphorylation of proteins involved in canonical oncogenic signaling networks, including ERK1/2 MAP kinases (T183/Y185 and T203/Y205 in the activation loop), PI3K regulatory subunit P85a, PDGFRα, and RTK scaffolds GAB1 and SHC, and cell cycle regulation (CDK1) were all increased in the tumor samples.…”
Section: Discussionsupporting
confidence: 55%
“…Reduced glutamate receptor phosphorylation, previously observed in GBM (35, 36), along with decreased phosphorylation of Dlg 2 (PSD-93), 3, and 4 (PSD-95) (37), and other neuron-specific proteins in our tumors likely reflect the differences in cellular composition between glioma and normal brain tissue (21). By comparison, phosphorylation of proteins involved in canonical oncogenic signaling networks, including ERK1/2 MAP kinases (T183/Y185 and T203/Y205 in the activation loop), PI3K regulatory subunit P85a, PDGFRα, and RTK scaffolds GAB1 and SHC, and cell cycle regulation (CDK1) were all increased in the tumor samples.…”
Section: Discussionsupporting
confidence: 55%
“…Relative to GluR1-GluR4 expression in primary astrocytes, quantitative analysis of GluR1-GluR4 transcript levels revealed the AMPA receptor subunits to be substantially downregulated in SMA-560, U87-MG and U373-MG glioma cells (Figure 4a), which might explain their lack of glutamate/AMPA responsiveness. A recent study revealed a complete lack of inward current in U87-MG cells following glutamate treatment, supporting this hypothesis (van Vuurden et al, 2009). In contrast, the transcript levels of GluR2 and GluR3 were severely increased in rat F98 and C6 glioma cells in comparison to primary astrocytes.…”
Section: Mechanisms Of Ampa Receptor Inactivation In Glioma Cellsmentioning
confidence: 60%
“…Conversely, overexpression of the unedited, Ca 2 þ permeable GluR2(Q) subunit augmented CGNH-89 glioma cell proliferation (Ishiuchi et al, 2002). In clear contrast to these studies, it has been recently suggested that glioma cells survive glutamate-rich, excitotoxic environment due to intrinsic glutamate receptor inactivation, which is supported by the finding that GluR subunits are transcriptionally downregulated in glioma specimens (van Vuurden et al, 2009). Owing to this caveat and the apparent importance of glutamate signaling for potential glioma therapy, we analyzed in detail the effects of genetic and pharmaco logical interference with glutamate secretion and cystine incorporation mediated by system X c À as well as glutamate receptor agonism and antagonism on glioma growth in vitro and ex vivo. We show that neither glutamate nor AMPA possesses any mitogenic effects on glioma cells even under growth factor-reduced or low-cystine conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Aronica et al demonstrated increased NR2A and NR2B (stimulatory NMDA receptor subunits) expression in 41 patients with LGG compared to controls [46]. Further, van Vuurden et al showed that oligodendrogliomas and astrocytomas exhibited greater AMPA-R expression than glioblastoma multiforme (GBM): that is, AMPA receptor expression appeared negatively correlated with WHO tumour grade [48]. In similar fashion, van Vuurden et al demonstrated significant down-regulation of NMDA (NR1, NR2A-C, NR3A), AMPA (GluR1-4) and kainite (GluR5,7; KA2) receptors (ionotropic receptors) in GBM compared to controls [48].…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…Further, van Vuurden et al showed that oligodendrogliomas and astrocytomas exhibited greater AMPA-R expression than glioblastoma multiforme (GBM): that is, AMPA receptor expression appeared negatively correlated with WHO tumour grade [48]. In similar fashion, van Vuurden et al demonstrated significant down-regulation of NMDA (NR1, NR2A-C, NR3A), AMPA (GluR1-4) and kainite (GluR5,7; KA2) receptors (ionotropic receptors) in GBM compared to controls [48]. Downregulation of AMPA-R, for example, enables GBM cells to survive a high glutamate environment without suffering excitotoxic cell death [48].…”
Section: Glutamate Receptorsmentioning
confidence: 99%